Pengelolaan Pembelajaran Kontekstual Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Negeri 24 Medan - Syafitri, Ardila; Mavianti, Mavianti (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
In contextual learning, the teacher brings real world situations into the classroom and encourages students to make connections between the knowledge they have and its application in their lives as members of the family and society. With this accepts, learning outcomes re expected to be moremeaningful for students. The learning process take place more naturally in the form of students work and experience activities, rather than the transfer of knowledge from teacher to students. In contextual classes, the teacher’s task is only to achieve the goal. Teachers deal more with strategy than giving information. Meanwhile, collecting fara uses interview, observation and documentation methods. The results of this study can be concluded that the management of Contextual Learning in Islamic Religious Education Subjects is very effective children in Learning at SMP Negeri 24 Medan.